2004
DOI: 10.1111/j.1365-2621.2004.tb09958.x
|View full text |Cite
|
Sign up to set email alerts
|

Preference Mapping of Commercial Chocolate Milks

Abstract: The dairy beverage market is a competitive and growing category in the food industry. Within this arena, chocolate milks vary widely in flavor, color, and viscosity. Understanding what sensory properties drive consumer liking is critical for maximum market share. This study was conducted to identify and define sensory characteristics of commercial chocolate milks and to link these differences to consumer preferences through the application of internal and external preference mapping. A sensory language was ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 20 publications
6
87
2
1
Order By: Relevance
“…To compare the class means two at a time, critical difference (C.D), also called least significant difference (LSD) was calculated as per the method described by Rangaswamy (1995). The same set of data were statistically analyzed using Xlstat software (version 2009) for principal component analysis to find out the components of prime importance, maximum positive loadings and their interaction with other attributes (Thompson et al 2004). For all statistical analyses, a value of p<0.05 was used as the criterion for statistical significance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To compare the class means two at a time, critical difference (C.D), also called least significant difference (LSD) was calculated as per the method described by Rangaswamy (1995). The same set of data were statistically analyzed using Xlstat software (version 2009) for principal component analysis to find out the components of prime importance, maximum positive loadings and their interaction with other attributes (Thompson et al 2004). For all statistical analyses, a value of p<0.05 was used as the criterion for statistical significance.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, defining the product with its characteristic features is an important criterion to evaluate the product precisely and specifically. Researchers have used descriptive analysis or specific attribute analysis (sensory characterization) to study aging and various processing parameters in cheese (Piggott and Mowat 1991;Drake et al 2001), whey and soy proteins (Drake et al 2007), emollients (Parente et al 2008), Malbec wines (Goldner and Zamora 2007), chocolate milks (Thompson et al 2004), beverages (Kappes et al 2006), soy milk (Keast and Lau 2006), and fermented food products (Ghosh and Chattopadhyay 2010) however, such studies have not been conducted on any of the traditional sweetmeats including doda burfi.…”
mentioning
confidence: 99%
“…Yuyama et al [44] found reduction in the caloric value ranged from 25.9% to 37.9% in jambolão fruit jams using four types of sweeteners individually or in combination (saccharin, cyclamate, acesulfame and St). Moreover, [45] [46] reported that stevioside give low calories.…”
Section: Nutritive Value Of Prepared Jamsmentioning
confidence: 99%
“…Table 6 gives sensory preference (color, flavor, sweetness, texture, overall liking) for the four chocolate milks. Color of chocolate milk sample containing sucrose and stevia -18g (B) and 20g (A) received 100% approval [21].…”
Section: Milksmentioning
confidence: 99%